Telemedicine Sebagai Platform Konsultasi Kesehatan Mental di Era Industri 4.0 - Rifqi Atsani; Galih Tyas Anjari (Assertive: Islamic Counseling Journal, 2023)
Telemedicine technology is a highly developed digital transformation in the health sector today. Telemedicine is widely used in various countries because of the perceived benefits of this technology, one of which is mental health. Mental health consultations with medical personnel can be done virtually or remotely. This study aims to determine the use of telemedicine in facilitating mental health problems. The design of this study used a literature review by looking at 13 articles which were then analyzed. The results of this study indicate that the use of telemedicine is influenced by cost factors, geographical factors, and ease of use factors affect the use of telemedicine for mental health consultations. The Covid-19 Pandemic has also caused a shift in treatment methods that use health facilities, some of which have switched to telemedicine due to divisions in activities and physical distancing. The cost factor is also related to telemedicine because patients who wish to consult about their health do not need to pay to visit a health facility. After all, it can be done online. The use of telemedicine greatly helps the geographical factors of people who are far from health facilities. Finally, the ease of use factor, because every element of society is now technologically literate, telemedicine will not be difficult. This study states that consultation or therapy via telemedicine has as good results as face-to-face therapy for mild and moderate mental health. However, a more in-depth research is needed for severe mental health conditions such as cognitive, behavioral, and sensory impairments.